2021
DOI: 10.1093/ajcn/nqab276
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics that modify the effect of small-quantity lipid-based nutrient supplementation on child anemia and micronutrient status: an individual participant data meta-analysis of randomized controlled trials

Abstract: Background Small-quantity lipid-based nutrient supplements (SQ-LNSs) have been shown to reduce the prevalence of child anemia and iron deficiency, but effects on other micronutrients are less well known. Identifying subgroups who benefit most from SQ-LNSs could support improved program design. Objectives We aimed to identify study-level and individual-level modifiers of the effect of SQ-LNSs on child hemoglobin (Hb), anemia, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 85 publications
3
18
0
Order By: Relevance
“…For severe wasting, the relative reduction due to SQ-LNS was 36% in sites with a high wasting burden, 34% in sites with a high stunting burden, 46% in sites with unimproved sanitation and 48% in sites with unimproved water quality. These findings suggest that targeting preventive SQ-LNS to high-risk populations may be warranted, which is consistent with the IPD analysis results for developmental outcomes (24) and hemoglobin (25).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For severe wasting, the relative reduction due to SQ-LNS was 36% in sites with a high wasting burden, 34% in sites with a high stunting burden, 46% in sites with unimproved sanitation and 48% in sites with unimproved water quality. These findings suggest that targeting preventive SQ-LNS to high-risk populations may be warranted, which is consistent with the IPD analysis results for developmental outcomes (24) and hemoglobin (25).…”
Section: Discussionsupporting
confidence: 85%
“…In a recent individual participant data (IPD) analysis of 14 randomized controlled trials, we found a 12-14% lower prevalence of stunting, wasting and underweight, as well as reductions in developmental delay, anemia and micronutrient deficiencies among children who received SQ-LNS during the complementary feeding period (22)(23)(24)(25). We did not include severe wasting or severe stunting in that set of analyses because we already had a large list of outcomes to examine, and also because a key objective of that work was examining individual-level effect modification, which is problematic for rare outcomes such as severe wasting.…”
Section: Introductionmentioning
confidence: 98%
“…Low iron stores from birth and iron-deficient diets put young children at increased risk for ID and anemia. The high burden of ID and anemia among Malawian infants and young children is concerning, and other interventions such as multiple micronutrient powders ( 44 ), lipid-based nutrient supplements ( 45 ), or promotion of other iron-rich foods such as small fish or chicken liver ( 46–48 ) are needed to address these issues. Additionally, any future nutrition-related interventions designed to address ID and anemia in this population are recommended to be implemented in conjunction with measures to control malaria and reduce inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reducing costs, targeting SQ-LNS to children in the most vulnerable communities could enhance effectiveness for certain outcomes. In the SQ-LNS meta-analyses, the impacts of SQ-LNS on development and iron status were greater among children with a higher burden of undernutrition or lower socio-economic status (4, 6).…”
Section: Discussionmentioning
confidence: 99%
“…These fortified food-based products (typically including vegetable oil, peanut paste, and milk powder) deliver vitamins and minerals as well as essential fatty acids and small amounts of energy (~100-120 kcal/day) and protein (1). Since the development of SQ-LNS ~15 years ago, a strong evidence base has been established demonstrating that SQ-LNS for children 6-24 months of age reduces child mortality, stunting, wasting, and anemia and promotes healthy development in efficacy trials as well as effectiveness trials in programmatic settings (2)(3)(4)(5)(6). As a result, SQ-LNS was listed in the 2021 Lancet Series on Maternal and Child Undernutrition as an intervention with a strong evidence base supporting implementation (7).…”
Section: Introductionmentioning
confidence: 99%